Proporsional Reasoning Matematics Student 4th Grade on Learning Cycle 5e Nuanced Ethnomatematics - Estanto, Doni; Zaenuri, Zaenuri; Junaedi, Iwan (Universitas Negeri Semarang, 2021)
The purpose of this study is to find the stages of students' mathematical proportional reasoning in learning cycle 5e nuanced ethnomathematics. The type of research used is mixed methods with concurrent embedded design. The population of this research is the students of SD IT Bunayya 2019/2020 Academic Year. The research subjects were students in grade IV, amounting to 20 children. Data collection techniques in the form of tests, interviews and documentation. The results showed that students' mathematical proportional reasoning in learning with learning cycle 5e nuanced ethnomathematics was grouped into three namely, students in the recognition of multiplicative relationships group, students in accommodating covariance and invariance groups, and students in functional and scalar relationships groups. In this study, students found obstacles in mathematical proportional reasoning that students have not been able to recognize additive and multiplicative relationships in understanding the similarity of ratios, recognizing rational plausibility, and have not been able to do unitizing. To address this, students need to be trained and understood about the concept of fractions worth and discuss about ratios that make sense.